Identifying house price diffusion patterns among Australian state capital cities - Liu, Chunlu; Luo, Zhen Qiang; Ma, Le; Picken, David (International Journal of Strategic Property Management, 2010)
Prior research supports the proposition that house price diffusion shows a ripple effect along the spatial dimension. That is, house price changes in one region would reflect in subsequent house price changes in other regions, showing certain linkages among regions. Using the vector autoregression model and the impulse response function, this study investigates house price diffusion among Australia's state capital cities, examining the response of one market to the innovation of other markets and determining the lagged terms for the maximum absolute value of the other markets’ responses. The results show that the most important sub‐national markets in Australia do not point to Sydney, rather towards Canberra and Hobart, while the Darwin market plays a role of buffer. The safest markets are Sydney and Melbourne. This study helps to predict house price movement trends in eight capital cities.First published online: 18 Oct 2010